The Spatial Distribution of Ankle Muscles Activity Discriminates Aged from Young Subjects during Standing - dos Anjos, Fabio V.; Pinto, Talita P.; Gazzoni, Marco; Vieira, Taian M. (Frontiers in Human Neuroscience, 2017)
During standing, age related differences in the activation of ankle muscles have been reported from surface electromyograms (EMGs) sampled locally. Given though activity seems to distribute unevenly within ankle muscles, the local sampling of surface EMGs may provide a biased view on how often and how much elderly and young individuals activate these muscles during standing. This study aimed therefore at sampling EMGs from multiple regions of individual ankle muscles to evaluate whether the distribution of muscle activity differs between aged and young subjects during standing. Thirteen young and eleven aged, healthy subjects were tested. Surface EMGs were sampled at multiple skin locations from tibialis anterior, soleus and medial and lateral gastrocnemius muscles while subjects stood at ease. The root mean square amplitude of EMGs was considered to estimate the duration, the degree of activity and the size of the muscle region where muscle activity was detected. Our main findings revealed the medial gastrocnemius was active for longer periods in aged (interquartile interval; 74.1-98.2%) than young (44.9-81.9%) individuals (P=0.02). Similarly, while tibialis anterior was rarely active in young (0.7-4.4%), in elderly subjects (2.6-82.5%) it was often recruited (P=0.01). Moreover, EMGs with relatively higher amplitude were detected over a significantly wider proximo-distal region of medial gastrocnemius in aged (29.4-45.6%) than young (20.1-31.3%) subjects (P=0.04). These results indicate the duration and the size of active muscle volume, as quantified from the spatial distribution of surface EMGs, discriminate well aged from young individuals during standing; elderlies seem to rely more heavily on the active loading of ankle muscles to control their standing posture than young individuals. Most importantly, current results suggest different conclusions on the active control of standing posture may be drawn depending on the skin location from where EMGs are collected, in particular for the medial gastrocnemius.